2018
DOI: 10.21037/jtd.2018.01.63
|View full text |Cite
|
Sign up to set email alerts
|

Sublobar resections for small-sized stage Ia lung adenocarcinoma: a Sino-Japanese multicenter study

Abstract: Background: Segmentectomy for small-sized stage Ia non-small cell lung cancer (NSCLC) may be comparable to lobectomy regarding prognosis and local recurrence. However, the clinical results of wedge resection for such patients are still under debate. In this international multicenter study, we retrospectively studied surgical outcomes of sublobar resections for patients with small-sized stage Ia adenocarcinoma to elucidate whether wedge resection is inferior to segmentectomy for such patients.Methods: Between M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…These 19 studies included four prospective studies and 15 retrospective studies. [3][4][5][6][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Table presents a summary of the extracted data. The number of patients treated by segmentectomy was lower than the number treated by wedge resection (3604 versus 10,593).…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These 19 studies included four prospective studies and 15 retrospective studies. [3][4][5][6][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Table presents a summary of the extracted data. The number of patients treated by segmentectomy was lower than the number treated by wedge resection (3604 versus 10,593).…”
Section: Search Resultsmentioning
confidence: 99%
“…A total of 15 studies (with 12,956 patients) reported OS after the surgical procedure (segmentectomy versus wedge resection). [3][4][5][6][14][15][16][17][22][23][24][25][26][27] Although, individually, only 4 of the 15 studies reported significantly better OS with segmentectomy than with wedge resection, 14,15,22,26 meta-analysis of all 15 studies confirmed that OS was indeed significantly better after segmentectomy (HR ¼ 0.82, 95% CI: 0.77-0.88; P < 0.001; Fig. 3A).…”
Section: Meta-analysismentioning
confidence: 87%
See 2 more Smart Citations
“…For these patients, lobectomy will result in greater loss of lung tissue and worse quality of life (QOL). Some trials have shown that segmentectomy has similar oncological outcomes to lobectomy for early‐stage NSCLC and results in better QOL . Both robotic surgery and video‐assisted thoracic surgery (VATS) are minimally invasive procedures for lung segmentectomy and can resect more lymph node stations and shorten the postoperative hospital stay compared to the open approach …”
Section: Introductionmentioning
confidence: 99%